2018
DOI: 10.1002/slct.201801624
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, Photophysical and Electrochemical Studies of Ruthenium(II) Complexes with 4′‐Substituted Terpyridine Ligands and Their Biological Applications

Abstract: Three 4′‐(4‐Methylbenzoate‐benzyloxy)‐2,2′:6′,2′′‐terpyridine (MBBtpy), 4′‐(4‐Ethylbenzoate‐benzyloxy)‐2,2′:6′,2′′‐terpyridine (EBBtpy) and 4′‐(5‐(1,3‐Dimethylbenzoate)‐benzyloxy)‐2,2′:6′,2′′‐terpyridine (DMBBtpy) ligands and seven ruthenium(II) symmetrical [Ru(MBBtpy)2](PF6)2 (Ru1), [Ru(EBBtpy)2](PF6)2 (Ru2), [Ru(DMBBtpy)2](PF6)2 (Ru3) and unsymmetrical [Ru(MBBtpy)(EBBtpy)](PF6)2 (Ru4), [Ru(MBBtpy)(ttpy)](PF6)2 (Ru5), [Ru(MBBtpy)(Brttpy)](PF6)2 (Ru6), [Ru(MBBtpy)(HOttpy)](PF6)2 (Ru7) complexes were synthesize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 57 publications
1
6
0
Order By: Relevance
“…The emission quantum yields (Φ em ) of the complexes 9, 10, and 11 in acetonitrile at room temperature (25 C) are 0.021, 0.026, and 0.016, respectively. TheΦ em values are within the range reported for Ru (II) complexes with 4 0 -substituted tpy [11] and bipyridine [28] but much lower than those reported for 4 0substituted di-tpy complexes. [44] These results demonstrate that the emission quantum yield depends on the nature of substituents at 4 0 -position of the ligand which influences the properties of Ru (II) tpy complexes.…”
Section: Photophysical Propertiessupporting
confidence: 78%
See 2 more Smart Citations
“…The emission quantum yields (Φ em ) of the complexes 9, 10, and 11 in acetonitrile at room temperature (25 C) are 0.021, 0.026, and 0.016, respectively. TheΦ em values are within the range reported for Ru (II) complexes with 4 0 -substituted tpy [11] and bipyridine [28] but much lower than those reported for 4 0substituted di-tpy complexes. [44] These results demonstrate that the emission quantum yield depends on the nature of substituents at 4 0 -position of the ligand which influences the properties of Ru (II) tpy complexes.…”
Section: Photophysical Propertiessupporting
confidence: 78%
“…In this regard, ruthenium (II/III) tpy complexes have been extensively investigated as anticancer and antimicrobial drugs as well as DNA binding agents. [9][10][11][12] In particular, in the design of innovative anticancer drugs, ruthenium tpy complexes have special consideration and have been evaluated against different cancer cell lines as promising alternates for the well-known diamine-dichloroplatinum (II) (cisplatin) and its derivatives. [13] Ruthenium accesses +2 and +3 oxidation states at physiological conditions and can bind to proteins, nucleic acids, sulfur, or oxygen-containing compounds in the cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been established that 2,2’:6’,2’’‐terpyridine has low quantum yield fluorescence and significant emission can be achieved after specific modification of the terpyridine, especially by introducing substituent at the 4’‐position . Huang et al.…”
Section: Introductionmentioning
confidence: 99%
“…It has been established that 2,2':6',2''-terpyridine has low quantum yield fluorescence [1] and significant emission can be achieved after specific modification of the terpyridine, [2] especially by introducing substituent at the 4'-position. [3][4][5][6] Huang et al also reported that intermolecular hydrogen bonds play an essential role in forming supramolcular networks of 4'chloro-2,2':6',2''-terpyridine hexafluorophosphorate in the solid state. [7] Terpyridine (terpy) is generally known to form trans-trans conformation.…”
Section: Introductionmentioning
confidence: 99%